A sequential utilization of the UV-A (365 nm) fluence rate for disinfection of water, contaminated with Legionella pneumophila and Legionelladumoffii. (1st July 2022) - Allahyari, Elaheh; Carraturo, Federica; De Risi, Arianna; Nappo, Antonio; Morelli, Michela; Cajora, Alessia; Guida, Marco
Abstract: Legionella species are the etiological agent of Legionnaires' disease, a pathology easily contracted from water circuits and by the inhalation of aerosol droplets. This bacterium mainly proliferates in water: Legionella pneumophila is the most commonly isolated specie in water environments and consequently in water system, although further Legionella species have frequently been isolated, including Legionella dumoffii. The simultaneous presence of the two species in the water system can therefore lead to the simultaneous infection of several people, giving rise to harmful outbreaks. Ultraviolet inactivation of waterborne microorganisms offers a rapid and effective treatment technique and recently is getting more attention mostly to eliminate unsafe level of contamination. To tackle the issue, the inactivation of the two species of Legionella spp., namely L. pneumophila and L. dumoffii, by means of UV-A light emitting diodes (UV-A LED) system is explored. We used a commercially available UV-A LED at 365 nm wavelength, and the UV-A dose is given incrementally to the Legionellae with a concentration of 10 6 CFU/mL in 0.9% NaCl (aq) solution. In this study, with a UV-A-dose of 1700 mJ/cm 2, the log-reduction of 3-log (99.9% inactivation) for L. pneumophila and 2.1-log (99.1% inactivation) for L. dumoffii of the contaminated water are achieved. The Electrical Energy per Order ( E EO ) is evaluated and showed this system is more economic and efficient in comparison with UV-C and UV-B LEDs. Following the support of this preliminary study with additional tests, aiming to validate the technology, we expect this device may be installed in water plants such as cooling systems or any water purification station in either industrial or home scales to reduce the risk of this infectious disease, preventing consumers' health. Graphical abstract: Image 1 Highlights: A method using LEDs at 365 nm to eliminate the Legionella spp. in water was tested. L. dumoffii is more resistant than L. pneumophila to the bacterial cell's damages. The inactivation kinetics of L. pneumophila and L. dumoffii by UV-A were calculated. The UVA-LEDs showed a higher Electrical Energy per Order compared to the UVC-LEDs.